Aspergillosis of the nose and paranasal sinuses. Issue 2 (February 1989) - Milroy, C M; Blanshard, J D; Lucas, S; Michaels, L
Abstract : Fulminant aspergillosis was diagnosed on nasal biopsy in a 49 year old man who had features of an aspergilloma. Further postmortem examination of this area was performed and the results were contrasted with the histological features of other Aspergillus infections. The nasal biopsy specimen and postmortem examination showed infiltrating Aspergillus hyphae with tissue necrosis and little inflammatory response. The hyphae were easily seen with routine stains. This contrasts with the findings in invasive aspergillosis where there is fibrosis and a granulomatous response to the Aspergillus hyphae. The hyphae are seen in giant cells using fungal stains. In the saprophytic infections aspergilloma and allergic Aspergillus sinusitis there is no tissue invasion or destruction. Aspergillus infections of the nose and paranasal sinuses often require biopsy for accurate diagnosis. As treatment varies pathologists need to be able to distinguish the different patterns of infection.